Breaking the academic silence: A cross-database analysis of early-career international scholars - Wang, ZiYang; Norhaini Mansor, Azlin; Amat, Salleh (Journal of International Students, 2026)
Structural inequalities in global academia shape the career prospects of early-career scholars, creating systemic barriers for internationally mobile scholars. This study characterizes core-periphery dynamics in knowledge production among early-career scholars and explores implications for transnational careers. Through a comparative bibliometric analysis of 282 articles from WoS and CNKI (2010–2025), we develop a double marginalization index that integrates spatial centrality and discursive power. The findings reveal entrenched asymmetries: WoS research shows theory-driven growth in Anglophone core regions, while CNKI scholars follow policy-cyclical patterns in elite eastern China. The index quantifies a persistent “double marginalization” of peripheral institutions, despite their active participation, with low visibility. This mapping elucidates the hierarchical field navigated by early-career scholars-especially internationally mobile students and researchers—linking geographic and discursive capital to uneven career trajectories. We conclude by calling for policies to foster equitable academic ecosystems.